The changes in mathematics education curriculum for a technical university in Malaysia - Khalid, Mohd Sazali (2013)
Today mathematics is regarded as an ordinary subject like languages even though it is the main core subject in engineering discipline. With IT applications, learning mathematics becomes simpler, faster and widely accepted. Currently, in the University Tun Hussein Onn Malaysia (UTHM) the total marks of the final mathematics examination comprised of 20% project done through group work. The objective of this paper is to demonstrate what the students had understood mathematics using experiential learning. The methodology used case studies of participants in a few statistics projects using 350 students (more than 60% girls) who were first year I.T. undergraduates within 3 months. A project was selected to determine why road users broke traffic rules. SPSS package was used to analyze descriptively and the participants confessed to enjoying social skills during data collection i.e., interviewing, designing, presenting and producing reports. As a result, delivering mathematics nowadays is quite different from 40 years ago.